Fungsionalisasi Al-Qur’an dalam Tradisi Pekan Keempat Bulan Safar di Kalimantan Barat - Parwanto, Wendi (SUHUF, 2024)
The main focus of this study is to explain the formulation or functionalization of the Al-Qur’an in the tradition of the fourth week in the Safar month in West Kalimantan, especially the people in Nuguk, Tebing Karangan Village (Melawi District) with the’ robo-robo’ tradition and the people in Parit Deraman Hulu (Kubu Raya District) with the ‘mandi Safar’ tradition. The type of this study is field research using the living Qur’an approach. The conclusion of this article explains that there are differences in the functional aspects of the Qur’an in the fourth week of the Safar month tradition. Regarding the ‘robo-robo’ traditions in Nuguk, Al-Qur’an has been used as a source of information and legalization for forming traditions. Meanwhile, in the ‘mandi safar’ tradition, the Qur’anic verses (parts of the verses of the Al-Qur’an) have been used as a source of practice manifested in real terms in the procession of carrying out the tradition. Secondly, on the aspect of agency transmission and the formation of traditions, in the ‘robo-robo’ tradition in Nuguk, the primary agency for the formation of traditions is the Qur’anic verses (Ali ‘Imran (3):103). Meanwhile, in the ‘mandi safar’ tradition in Parit Deraman Hulu, the primary actor in formulating this tradition was the behavior of religious elite figures, namely Syekh Ismail Mundu.